Tradisi Upacara Memayu dan Ider-Ideran Trusmi Kabupaten Cirebon Jawa Barat - Neneng Lestari (Thaqafiyyat : Jurnal Bahasa, Peradaban dan Informasi Islam, 2013)
This paper aims to reveal the historical background of the emergence of traditions and ceremonies memayu and ider - ideran Trusmi, and the reason why the tradition still survives and sustainable amid modern society has today. To discuss both the subject matter, the author uses the theory of functionalism Bronislow Malinowski. Data were collected through observations, interviews and documentation. The approach used is qualitative method. From the results of this study found that Trusmi name is formed from two words, which continues and spring means constantly growing. The origins of this name originated from the story of Ki Gede Bambangan who was sitting in front of his cabin after cleaning the yard of grass. Suddenly there are greetings that do not know exactly where it comes from that voice. Then miraculously suddenly all the grass and weeds that had already cleared it grows back so pruning becomes useless. When he looked around with astonishment mingled irritation, suddenly, two men are walking towards him while greeting, "Assalamu" Sounds Sapan was apparently derived from the prince Cakra Buana and Sunan Gunung Jati. Ultimately stems from the peristiwa Ki Gede Bambangaan embraced Islam andis called Trusmi area. That is an area where the grass is constantly growing back. Special on Trusmi Mosque, memayu ceremony performed to replace the roof of the mosque which was made of welit as tiled and wood as their frames. Welit replacement was performed in preparation for the change of seasons from the dry to the rainy season. One year as a number welit periodic replacement. Furthermore memayu also serve as a means for society as earth alms - area three to start the season. The hope someday to give blessings and harvest will be successful. Regardless of people's beliefs about memayu , this rite is an expression of ingratitude given God Almighty . Therefore it can be concluded that the tradition memayu and ider - ideran Trusmi village is a series of sacred rituals which also includes the values of culture that to this day is still preserved by the Cirebon people, especially the villagers Trusmi .